Geomechanical characterization of mechanical properties and in-situ stresses for predicting wellbore stability of ATG-field, A case study: Niger delta petroleum province, Nigeria - Abraham Sunu, Sebastian; Sunday Oniku, Adetola; Chukwudi Meludu, Osita; Patrick Abbey, Chukwuemeka (International Journal of Advanced Geosciences, 2020)
Well logs from ATG- field wells ATG-10 and ATG-11 were calibrated to develop Mechanical Earth Model (MEM) based on elastic parameter, failure parameters, in-situ stresses, pore pressure using well logs to predict wellbore failure. Poisson’s ratio derived from compressional and shear velocities interval transit time and density logs (RHOB), showed that the values ranges from 0.17 to 0.48 and 0.09 to 0.49, and the dynamic Young's Modulus derived from the Compressional and Shear velocity Logs, ranges from 6.0 GPa to 7.8 GPa and 3.6 GPa to 6.6 GPa, the dynamic shear modulus derived from dynamic young’s modulus and Poisson’s ratio which ranges from 3.8 GPa to 5.1 GPa and 2.1 GPa to 5.4 GPa, while the dynamic Bulk modulus ranges from 0.25 GPa to 1.67 GPa and 0.43 GPa to 1.18 GPa for wells ATG-10 and ATG-11 respectively. The calibrated failure parameters or rock strengths derived from compressional velocity logs include: the internal friction angle (ϕ) from Plumb’s correlation, these ranges from 20.869o to 65.5o and 20.869o to 45.61o, Unaxial compressive (UCS) strength ranges from 757.837 psi to 2505.836 psi and 4577.099 psi to 10512.876 psi, cohesion Strength (C) ranges from 205.697 psi to 355.308 psi and 70.652 psi to 390.32 psi and Tensile strength (To) varies from 17.141 psi to 29.609 psi and 5.885 psi to 32.527 psi for well ATG-10 and ATG-11 respectively. The elastic and rock strengths properties vary in a similar trend to the sonic logs as they are derived based on these values. These properties show increasing values with increasing depth, as a result of larger overburden stress, hence lower porosity or high compressional velocity of the formations. However, the elastic properties and formation strength may vary in different formations.